Climate change and health as massive open online courses - Barteit, Sandra; Sauerborn, Rainer (Building continents of knowledge in oceans of data, 2018)
To teach the basics of climate change and health - such as the nature of health impacts, best practices in adoption strategies and promotion in health co-benefits, mitigation and adaptation strategies - we have developed three massive open online courses (MOOCs). We analysed the three MOOCs with regards to different factors such as course content, student motivation, instructor behaviour, co-learner effects, design and implementation effects. We conducted online surveys for all three MOOCs based on the research model of Hone et al., extended with regards to student's motivation and course outcomes. In total, we evaluated 6898 students, of which 101 students took part in the online survey. We found differences in completion rates and country of origin for the three MOOCs. The francophone MOOC was found to have a high number of participants from lower-income- and low-and-middle-income countries. The majority of participants were aged between 22 and 40 years of age and had mainly a graduate educational background. The primary motivation to join the MOOC was the knowledge and skills gained as a result of taking the course. The three MOOCs on climate change and health had a reach of almost 7000 students worldwide, as compared to the scope of a face-to-face course on the same topic of 30 students, including students from resource-low environments that are already vulnerable to current changes in climate. The evaluation of the MOOCs outlined the current impact. However, further research has to be conducted to be able to get insights into the impact over time.
Gesehen am 05.03.2020